ANALISIS SISTEM KOMUNIKASI PENUNJANG EKONOMI KREATIF BERBASIS POTENSI LOKAL (STUDI KASUS KOMUNITAS BANDUNG CREATIVE CITY FORUM (BCCF)) - Dea Christina; Muhammad Zaini Dahlan (Universitas Muhammadiyah Jakarta, 2018)
Development focus has been evolved. Nowadays, we are in the Age of Creative Economy which mobilized mostly by Creative Industry. However, Indonesia has benefited in terms of developing this sector, since it has 2 acknowledged advantages, such as demographic segmentation and ecosystem buffer and support. Unfortunately, it is not enough to make ideal and successful creative ecosystem. Communication in the system should also be developed. BCCF is a supporting communication system in the level of city, who can be an agent of change and a creative hub between stakeholder and community. Still, it has limitation. To give some recommendation to improve the communication process in this supporting communication system is the purposes of this paper. Blackbox analysis shows there are some elements in the system such as, controllable input, uncontrollable input, management, environment, controllable output and uncontrollable output. We should highlight uncontrollable input like youth motivation, community readiness and stakeholder commitment which are easily up and down. It will influence how the system achievement, gaining expected output or unexpected output. Based on the analysis, the communication strategy should refer to communication managerial. It means communication process must be appropriated with the most user in the system, which is the youth. Keywords: communication system, creative economy, local potential